62.0k views
2 votes
Rearange the equation so n is the independent variable m+1=-2n+6 ? M= what

1 Answer

4 votes

Answer:

m = - 2n + 5

Explanation:

Given the equation:

m+1=-2n+6

Rearrange the equation so that n is the independent variable

The independent variable is the predictor variable, Hence causes a change in the value of predicted variable obtained.

m+1=-2n+6

m = - 2n + 6 - 1

m = - 2n + 5

m = - 2n + 5

The general form of a regression equation:

y = ax + b

Where y = dependent variable

x = independent variable ; a = Coefficient of slope ; b = intercept

Hence, the equation : m = - 2n + 5

User Shaleen
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.